Travesty of Urban Little Russia in Travelogue “Famous Drums Beyond Mountains, or My Journey Somewhere in 1810” by I. M. Dolgorukov - S. S. Zhdanov (Научный диалог, 2024)
This study explores the representation of cities in Little Russia as depicted in I. M. Dolgorukov’s travelogue “Famous Drums Beyond the Mountains, or My Journey Somewhere in 1810” through a semiotic and imagological lens. The relevance of this research is underscored by the growing interest in Ukrainian identity within contemporary literary studies, particularly concerning its spatial dimensions, which remain underexplored. Consequently, this study offers a novel analysis of the urban imagery of Little Russia, focusing on descriptions of Kharkiv, Poltava, and Kyiv. Notable trends of estrangement and travesty emerge in the portrayal of these cities, alongside recurring motifs of alienation within the Little Russian landscape and a nostalgic yearning for belonging. A significant aspect of the narrative is the history of the Dolgorukov family, intricately linked to the topos of Little Russia, particularly Kyiv, where the author’s grandmother and uncle passed away. The city’s depiction is marked by themes of allure, orderliness, grandeur, wealth, antiquity, glory, and sacredness, some of which are subject to travesty. The spaces of Kharkiv and Poltava are presented as ambivalent provincial toposes characterized by both ordered and entropic qualities. The orderliness of Kharkiv is associated with descriptions of educational loci, while the positive motifs of Poltava relate to the realm of historical memory.